Glycoengineered cell models for the characterization of cancer O-glycoproteome: an innovative strategy for biomarker discovery. (August 2015) - Campos, Diana; Freitas, Daniela; Gomes, Joana; Reis, Celso A
<x xml:space="preserve">Abstract</x> Glycosylation is one of the most abundant forms of protein posttranslational modification. O-glycosylation is a major type of protein glycosylation, comprising different types and structures expressed in several physiologic and pathologic conditions. The understanding of protein attachment site and glycan structure is of the utmost importance for the clarification of the role glycosylation plays in normal cells and in pathological conditions. Neoplastic transformation frequently shows the expression of immature truncated O-glycans. These aberrantly expressed O-glycans have been shown to induce oncogenic properties and can be detected in premalignant lesions, meaning that they are an important source of biomarkers. This article addresses the recent application of genetically engineered cancer cell models to produce simplified homogenous O-glycans allowing the characterization of cancer cells O-glycoproteomes, using advanced mass spectrometry methods and the identification of potential cancer-specific O-glycosylation sites. This article will also discuss possible applications of these biomarkers in the cancer field.